THE ROLE OF THINK TANKS (Journal of the Spanish Institute for Strategic Studies, 2018)
This article aims to analyse the role of think tanks (organisations that produce ideas or solutions for the implementation of public policies) in the field of defence and international relations. Think tanks are key players in managing defence policies and developing operational military strategies in a complex and globalized environment; an environment marked by a democracy of opinion which is increasingly conditioned by the importance of mass media, shared governance, consensus, negotiation and balance of powers.